FIGURATIVE LANGUAGE IN THE ALBUM “GOOD LUCK TO YOU, GIRL SCOUT!” BY THE BLACK SKIRTS - Ave Lucia Nadeak (ELTR Journal, 2023)
Language allows humans to communicate by sending explicit or implicit messages. Figurative language is used to communicate indirectly in literature. A song that uses figurative language may confuse the listener with the meaning. This study investigated figurative language and the meaning of six songs from the album " Good Luck to You, Girl Scout!" There are two research questions: 1) What types of figurative language are used in the album "Good Luck to You, Girl Scout" by The Black Skirts? 2) What does The Black Skirts' album "Good Luck to You, Girl Scout!" figurative language mean? The researcher used Perrine’s theory (1977) and Leech’s theory (1981) to answer the research questions. Qualitative research was used to gather and analyze data from the album's lyrics. The study found metaphor, simile, personification, apostrophe, synecdoche, metonymy, symbol, hyperbole, and allusion. The implications of the usage of figurative language were exposed when the researcher determined the type, and it turns out that this song album was about heartbreak, betrayal, and longing for a lover or ex-lover.